Author Correction: Preserved wake-dependent cortical excitability dynamics predict cognitive fitness beyond age-related brain alterations - Maxime Van Egroo (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s42003-021-01995-5